Effectiveness of Macroprudential Policy on Banking Credit Growth in Indonesia (2015-2023) - Cendani, Marita Asri; Puspitasari, Inda Fresti (Journal of Economics Research and Social Sciences, 2025)
The COVID-19 pandemic shows that macroprudential policy is one of the crucial instruments in mitigating economic shocks and ensuring the financial system. This study examines the effectiveness of macroprudential policies on banking credit growth in Indonesia from 2015 to 2023 by analyzing the impact of the Debt-to-Income Ratio (DTI), Minimum Reserve Requirement (GWM), Capital Adequacy Ratio (CAR), and Non-Performing Loans (NPL). This study aims to give regulators insights into optimizing policy combinations to mitigate financial risks while supporting sustainable economic growth. The results of panel data regression revealed that DTI and CAR significantly impact banking credit growth. In contrast, GWM and NPL didn’t have a significant effect. These findings emphasize the critical role of macroprudential policies in maintaining a balance between credit growth and financial stability, especially in times of economic uncertainty. This study contributes to policymakers and financial regulators optimizing macroprudential frameworks to enhance financial resilience and support sustainable credit distribution in Indonesia’s banking sector.